Sandwiching of MOF nanoparticles between graphene oxide nanosheets among ice grains - Youhua Lu; Ye-Guang Fang; Yang Chen; Han Xue; Junqiang Mao; Bo Guan; Jie Liu; Jinping Li; Libo Li; Chongqin Zhu; Wei-Hai Fang; Thomas P. Russell; et al. (Nature Communications)
Abstract Current strategies to tailor the formation of nanoparticle clusters require specificity and directionality built into the surface functionalization of the nanoparticles by involved chemistries that can alter their properties. Here, we describe a non-disruptive approach to place nanomaterials of different shapes between nanosheets, i.e., nano-sandwiches, absent any pre-modification of the components. We demonstrate this with metal-organic frameworks (MOFs) and silicon oxide (SiO2) nanoparticles sandwiched between graphene oxide (GO) nanosheets, MOF-GO and SiO2-GO, respectively. For the MOF-GO, the MOF shows significantly enhanced conductivity and retains its original crystallinity, even after one-year exposure to aqueous acid/base solutions, where the GO effectively encapsulates the MOF, shielding it from polar molecules and ions. The MOF-GOs are shown to effectively capture CO2 from a high-humidity flue gas while fully maintaining their crystallinities and porosities. Similar behavior is found for other MOFs, including water-sensitive HKUST-1 and MOF-5, promoting the use of MOFs in practical applications. The nanoparticle sandwich strategy provides opportunities for materials science in the design of nanoparticle clusters consisting of different materials and shapes with predetermined spatial arrangements.